AN ANALYSIS ON ELT MATERIALS AS A REFERENCE SOURCE - Syarifah Aminah; Regina Regina; Y. Gatot Sutapa (ICoTE Proceedings, 2018)
Teaching materials used in schools are various. Coursebooks are books used in colleges or schools as teaching guideline. The tasks presented in a coursebook should fit three basic components; they are the curriculum, the students, and the teachers. İn this study, the researcher only focus on a coursebook fits the students. In order to fit the students’ need, a textbook should consider four things, such as content/explanation, examples, exercises/tasks, and presentation/format. The latest curriculum in Indonesia which is curriculum 2013 requires English teachers to implement a new coursebook. Therefore, the explanation of coursebook materials shuoulb be clear and understandable. Hence, the writer aimed this study to investigate the presented explanation of grammar materials in the latest revised English Coursebook of grade tenth. Whether the explanation can help the students achieve the learning objectives. This study was a content analysis study which analyses the content of a coursebook. The result of the study revealed that this coursebook is quite simple yet it does not consist of clear explanations on the grammar materials part. Moreover, some interactive teaching strategies are presented in the coursebook. Some language use and languge form also emphasizes in the coursebook.